Ultra performance liquid chromatography mass spectrometry : evaluation and applications in food analysis - Naushad, Mu; Khan, Mohammad Rizwan (CRC Press, Taylor & Francis Group, 2014)
"This book presents a unique collection of up-to-date UPLC-MS/MS methods for the separation and quantitative determination of carbohydrates, lipids, proteins, peptides, amino acids, vitamins, aroma and flavor compounds in a wide variety of foods and food products. The book provides practical information to those who are involved in the research and development, production, or routing analysis of foods and food products"--